Household income and academic performance in Korean adolescents: A longitudinal test of dual investment pathways - Ran Kang (PLoS ONE, 2026)
Building on the Family Investment Model (FIM), the present study examined how household income shapes adolescents’ academic performance through material and relational investments within the Korean educational context. Drawing on three waves of data from the nationally representative Korean Children and Youth Panel Survey 2018 (N = 2,387), we estimated a longitudinal parallel mediation model that accounted for baseline levels of each construct and demographic covariates. Results indicated that household income predicted higher private educational expenditure but was not associated with parent–child communication. Indirect effects revealed that household income influenced academic performance through material investment in private education, whereas the relational pathway was not significant. However, the difference between the two indirect pathways did not reach statistical significance. These findings suggest that private educational expenditure may represent one important pathway linking family economic resources to adolescents’ perceived academic performance in the Korean educational context. These findings underscore how household economic resources are differentially converted into educational advantages through family investment processes, highlighting implications for understanding income-based educational stratification in highly competitive educational contexts.